Exposure to air pollution in indoor walkways of a suburban city. (October 2020) - Li, Linhao; Mullan, Aidan F.; Clements, Nicholas
Abstract: Indoor walkways are often connected to sources of indoor pollutants such as retail stores, restaurants, and parking garages. To measure the air quality within indoor skyways and subways in downtown Rochester, MN, a mobile monitoring platform was deployed at least once per month for one year. Nineteen segments of each walkway type were measured for 5-min intervals twice per sampling day. Adjacent storefront or building type did not significantly impact air pollution concentrations measured in walkway segments; however, trends were observed in some spatial comparisons. Segments adjacent to restaurants had elevated PM2.5, TVOC, and CO2 concentrations, while elevated O3 and PM10-2.5 concentrations occurred adjacent to parking garages and streets. Inhalation dose was simulated for a range of walking routes for a baseline distribution of exposure, estimated for a healthy middle-aged adult male walking all identified routes. Compared to this baseline case, exposure increased by 179–457% (p < 0.001, all pollutants) when dining; by 15–18% (p < 0.001, all pollutants) for an elderly population; and by 11–37% (p < 0.001, all pollutants) during annual peak concentration periods. Low levels of air pollution are being maintained in the measured indoor walkways, and personal exposure can be significantly reduced by avoiding restaurant-dense areas around mealtimes. Graphical abstract: Image 1 Highlights: Adjacent storefront type did not significantly impact pollutant concentrations, though spatial trends were observed. Air pollution concentrations were significantly higher during source region sampling compared to the spatial sampling. PM2.5, PM10-2.5, and TVOC concentrations temporally peaked in cold months, while O3 concentrations peaked during warm months. Median inhalation exposure significantly increased for the elderly, when dining, and during seasonal pollutant peaks.